Assessing costs and benefits of early childhood intervention programs : overview and application to the Starting Early Starting Smart program - Karoly, Lynn A., 1961-; Kilburn, M. Rebecca; Bigelow, James H.; Caulkins, Jonathan P. (Jonathan Paul), 1965-; Cannon, Jill S.; Rand eBooks (Santa Monica, CA : RAND, 2001)
Does money invested early in a child's life pay dividends in the form of government savings or other societal benefits as he or she grows into adulthood? Is there a best method for determining what, if any, dividends have accrued? The authors identify the conceptual and methodological issues associated with the analysis of costs and outcomes of early intervention programs and review the prior application of these methods to several programs. This background leads to recommendations regarding the application of these tools for a particular public-private early intervention program, Starting Early Starting Smart (SESS). SESS was designed to test the effectiveness of integrating behavioral health services within primary care and early childhood service settings for children from birth to age seven. The specific recommendations are framed as a set of more general guidelines for decisionmakers to make choices about early childhood intervention programs.
Introduction -- Overview of Cost and Outcome Analysis -- Issues in Cost and Outcome Analysis of Early Childhood Intervention Programs -- Benefit-Cost Findings for Early Childhood Intervention Programs -- Applying Cost and Outcome Analysis to the Starting Early Starting Smart Program -- Conclusions -- Appendix A: Starting Early Starting Smart Grant Sites -- Appendix B: SESS Program Acknowledgments -- Appendix C: Mission Statements of the National Collaborators.
"Spring 2001."
Includes bibliographical references (p. 131-138).
Also available on the internet via WWW in PDF format.
Keywords: Starting Early Starting Smart (Program); Child development -- United States; Child mental health services -- United States -- Evaluation; Child welfare -- United States -- Evaluation; Children -- Drug use -- United States -- Evaluation; Children -- Services for -- United States -- Cost effectiveness; Early childhood education -- United States -- Evaluation; Electronic books